Nurturing Professional Development in TESOL: A Community of Practice Perspective - Gougou, Saman Ange-Michel; Paschal, Mahona Joseph (CV. Literasi Indonesia, 2024)
The focus of this paper was to explore the challenges facing the effectiveness of teaching the English Language in TESOL and assess the role of communities of practice groups in overcoming challenges facing the effectiveness of teaching the English Language in East and West Africa. The study employed qualitative research through a virtual ethnography approach. Data were collected through participative observation and interviews in communities of practices and platforms online. Findings established that lack of teaching materials, poor teaching environment, and lack of opportunities for a Community of Practice and professional development were among the challenges that have been hindering the effectiveness of teaching the English Language in the field of TESOL in East and West Africa. Online professional development offered by Community of Practice groups, sharing English teaching materials, and opportunities to support school-based teacher education and training were among the strategies revealed by Community of Practice used by teachers to improve their teaching in TESOL. As a result, the study recommends that cultivating communities of practice and sharing professional development opportunities provide a continuous learning support system for updating English teaching strategies and providing effective skill acquisition in a sustainable and inclusive educational system.